Microsurgical head and neck tissue repair by visceral mini-autografting - A. D. Kaprin; I. V. Reshetov; M. V. Ratushnyi; S. A. Kravtsov; A. P. Polyakov; O. V. Matorin; F. E. Sevryukov; M. M. Filyushin; V. N. Vasilyev; I. V. Rebrikova (Опухоли головы и шеи)
Objective. To minimize surgical trauma in patients with head and neck tumors during microsurgical plasty with visceral autografts.Subjects and methods. Clinical experience has been gained in the treatment of 53 patients with locally advanced craniofascial (n = 27) and oropharyngeal (n = 36) cancers. Abdominal organs were used for plastic closure of extensive defects after surgical resection. Paraumbilical incision allowing for an adequate approach into the abdominal cavity with minimal external trauma in the anterior abdominal wall was chosen as an access procedure. Video-assisted techniques were used to excise the midline aponeurosis. Donor organs, such as the omentum, greater curvature of the stomach, transverse colon, small intestine) were taken through a mini-laparotomic incision to the anterior abdominal wall, then the vascular pedicle was exposed and a visceral autograft was made. After forming and cutting off the autograft, organ anastomoses were created extracorporeally.Results. Mini-access surgery could be completed in 50 of the 53 cases (4 patients had previously undergone abdominal interventions). Omental (n = 26), colo-omental (n = 15), gastro-omental (n = 7), and entero-omental (n = 5) flaps were made and prepared for autografting. No intra- or postoperative abdominal complications were found.Conclusion. Minimally invasive technologies used to create visceral authografts for head and neck tissue repair can minimize surgical trauma and reduce treatment duration. The indications for this access are the debilitating state of a cancer patient or the young age of a patient who does not wish to have an additional scar in the donor region.